Interactions of Lactobacilli with Pathogenic Streptococcus pyogenes - Mark L. Westbroek; Crystal L. Davis; Lena S. Fawson; Travis M. Price (Hindawi Limited, 2010)
Objective. To determine whether (1) a decreased concentration of Lactobacilli allows S. pyogenes to grow; (2) S. pyogenes is able to grow in the presence of healthy Lactobacillus concentrations; (3) S. pyogenes is capable of inhibiting Lactobacilli. Methods. One hundred fifty patient samples of S. pyogenes were mixed with four different concentrations of L. crispatus and L. jensenii. Colony counts and pH measurements were taken from these concentrations and compared using t-tests and ANOVA statistical analyses. Results. Statistical tests showed no significant difference between the colony counts of S. pyogenes by itself and growth when mixed with Lactobacilli, and no significant difference between the colony counts of S. pyogenes in the four different concentrations of Lactobacilli. Conclusion. The statistical data representing the growth of these two organisms suggests that Lactobacilli did not inhibit the growth of S. pyogenes. Also, S. pyogenes did not inhibit the growth of Lactobacilli.